Implikasi Pendidikan dari Q.S An-Nisa Ayat 1 tentang Silaturahim terhadap Pendidikan Sosial - Sri Wulandari; Aep Saepudin (UNISBA Press, 2022)
Abstract. Difficulty in socializing with someone has an impact on being a quiet person, shy, difficult to control himself and likes to withdraw from group activities. This social behavior is caused by the first external factors in the family environment in the form of the relationship between parents and their children, how to educate, and the atmosphere in the house. As social beings who need each other, it is necessary to establish good relations with humans through friendship in order to understand their social environment. This study aims to (1) find out the opinion of the commentators regarding Q.S An-Nisa verse 1, (2) find out the essence contained in Q.S. An-Nisa verse 1, (3) Knowing the opinion of experts regarding social education, (4) Understanding of educational implications of Q.S An-Nisa verse 1 regarding friendship on social education. In this study, the author uses a qualitative approach with library research techniques using descriptive analysis and the tahlili method, by interpreting the existing data. The object of this research is interpretation. The results of this study can be concluded that the essence contained in QS An-Nisa paragraph 1 (1) piety as a basis for doing friendship, (2) silarurahim values that must be fostered in social education, (3) quality social education starts with the nuclear family, and (4) The establishment of social education by maintaining kinship ties and the rights of relatives and prohibiting breaking them. The educational implications of QS An-Nisa verse 1 (1) (1) Taaruf, (2) Tafahum, and (3) Ta’awun. Abstrak. Kesulitan dalam bersosialisasi terhadap seseorang berdampak menjadi pribadi yang pendiam, pemalu, sulit untuk mengontrol diri dan suka menarik diri dari kegiatan-kegiatan kelompok. Perilaku sosial ini disebabkan oleh faktor eksternal yang pertama ada pada lingkungan keluarga berupa hubungan orang tua dengan anaknya, cara mendidik, dan suasana dalam rumah. Sebagai makhluk sosial yang saling membutuhkan satu sama lain, maka perlu menjalin hubungan baik dengan manusia melalui silaturahim agar memahami lingkungan sosialnya. Penelitian ini bertujuan untuk (1) Mengetahui pendapat para mufasir mengenai Q.S An-Nisa ayat 1, (2) Mengetahui esensi yang terkandung dalam Q.S. An-Nisa ayat 1, (3) Mengetahui pendapat para ahli mengenai pendidikan sosial, (4) Memahami implikasi pendidikan dari Q.S An-Nisa ayat 1 tentang silaturahim terhadap pendidikan sosial. Dalam penelitian ini penulis menggunakan pendekatan kualitatif dengan teknik library research menggunakan deskriptif analisis dan metode tahlili, dengan cara menafsirkan data yang ada. Objek yang dijadikan penelitian ini adalah tafsir. Hasil penelitian ini dapat disimpulkan bahwa Esensi yang terkandung dalam Q.S An-Nisa ayat 1 (1) Takwa sebagai landasan dalam melakukan silaturrahim, (2) Nilai-nilai silarurahim yang harus dibina dalam pendidikan sosial, (3) Pendidikan sosial yang berkualitas dimulai keluarga inti, dan (4) Terbentuknya pendidikan sosial dengan cara memelihara ikatan kekerabatan dan hak kerabat serta melarang untuk memutuskannya. Adapun Implikasi pendidikan dari Q.S An-Nisa ayat 1 (1) Taaruf, (2) Tafahum, dan (3) Ta’awun.